Lifelong learning in reality : the perception of the community - Wardah Mohamad; Wan Rohaida Wan Husin; Zulhairi Zakariah; Nor Zafira Abu (2014)
Lifelong learning is an important part of the education system in Malaysia and has been implemented in various sectors of the economy. It has been used as a tool to promote learning in order to transform the country into a knowledge economy. Lifelong learning has taken various forms from formal education to informal classes, from long term to short term and from face-to-face classes, blended classes to fully online classes. This research presents the findings from community focus groups which were held over a few months in various locations in the country. The objective of the research was to gauge the perception of the community regarding lifelong learning in Malaysia. Data was analysed through reduction analysis and reported in narrative form. Findings reported differences in opinion regarding the modes of learning, the curriculum offered, the attitudes of learners and the objective of taking up lifelong learning. Other issues brought up included the financial aspects of lifelong learning and also the culture and values of lifelong learners. The paper concludes by giving recommendations for improvements based on the analysis given. (Abstract by authors)